Analysis of modern sports marketing of post-Olympic era - Wang, H. (Journal of Human Sport & Exercise, 2011)
There is a long history for sports as a marketing vehicle. With enormous business opportunities and expanding market, Chinese enterprises, large and small, are taking advantages of "in-depth marketing" to build their brand names with all their resources and promote sustained development of modern sports marketing.